Analisis Kontribusi Pajak Daerah Terhadap Pendapatan Asli Daerah Kabupaten Sikka Tahun 2013-2017 - Antonius Philipus Kurniawan Gheta (RELASI : JURNAL EKONOMI, 2020)
This study aims to calculate the level of contribution, to analyze the growth rate oflocal tax revenues on the indigenous revenue of Sikka Regency from 2013 to 2017 and To know the extent of the tax acceptance rates S ikka Regency period 2018 until 2022. . The research methods used in this study are descriptive research methods with a quantitative approach to getting a clearer and more detailed picture of a state based on the data or information that has been obtained. The results of the research obtained by the average regional tax contribution to the original revenue of S ikka Regency from 2013-2017 (5 years) by 14.27%. These results indicate that the level of regional tax contributions to the indigenous revenue of S ikka regency from 2013-2017 in the criteria of less co ntributing to the local revenue. The average rate of growth in S ikka District tax is 2013-2017, which amounted to 16.2%. This shows that the local tax growth of S ikka Regency is included in the less successful criteria. The results of the projected calculation of regional tax revenues for the next five years, 2018-2022 are expected to continue to increase annually. In 2018 predictions of S ikka district tax revenues amounted to Rp 15,960,932,070.345. In 2019 the prediction of local tax revenues amounted to Rp 17,514,147,581.89 and in 2020 the predicted regional tax revenue of Rp 19,067,363,093.435. The regional tax prediction of S ikka Regency in 2021 amounted to Rp 20,620,578,604.98, while in 2022 the regional tax revenues of Sikka Regency were predicted Rp22,173,794,116.525